Longitudinal Changes in Hippocampal Network Connectivity in Alzheimer's Disease. Issue 3 (6th August 2021) - Dautricourt, Sophie; de Flores, Robin; Landeau, Brigitte; Poisnel, Géraldine; Vanhoutte, Matthieu; Delcroix, Nicolas; Eustache, Francis; Vivien, Denis; de la Sayette, Vincent; Chételat, Gaël
Abstract : Objective: The hippocampus is connected to 2 distinct cortical brain networks, the posterior–medial and the anterior–temporal networks, involving different medial temporal lobe (MTL) subregions. The aim of this study was to assess the functional alterations of these 2 networks, their changes over time, and links to cognition in Alzheimer's disease. Methods: We assessed MTL connectivity in 53 amyloid‐β–positive patients with mild cognitive impairment and AD dementia and 68 healthy elderly controls, using resting‐state functional magnetic resonance imaging, cross‐sectionally and longitudinally. First, we compared the functional connectivity of the posterior–medial and anterior–temporal networks within the control group to highlight their specificities. Second, we compared the connectivity of these networks between groups, and between baseline and 18‐month follow‐up in patients. Third, we assessed the association in the connectivity changes between the 2 networks, and with cognitive performance. Results: We found decreased connectivity in patients specifically between the hippocampus and the posterior–medial network, together with increased connectivity between several MTL subregions and the anterior–temporal network. Moreover, changes in the posterior–medial and anterior–temporal networks were interrelated such that decreased MTL–posterior–medial connectivity was associated with increased MTL–anterior–temporal connectivity. Finally, both MTL–posterior–medial decrease and MTL–anterior–temporal increase predicted cognitive decline. Interpretation: Our findings demonstrate that longitudinal connectivity changes in the posterior–medial and anterior–temporal hippocampal networks are linked together and that they both contribute to cognitive decline in Alzheimer's disease. These results shed light on the critical role of the posterior–medial and anterior–temporal networks in Alzheimer's disease pathophysiology and clinical symptoms. ANN NEUROL 2021;90:391–406